2021
DOI: 10.3389/fpsyg.2021.647837
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Music for Emotional Wellbeing During the COVID-19 Lockdown in Spain: An Analysis of Personal and Context-Related Variables

Abstract: The strict lockdown experienced in Spain during March–June 2020 as a consequence of the COVID-19 crisis has led to strong negative emotions. Music can contribute to enhancing wellbeing, but the extent of this effect may be modulated by both personal and context-related variables. This study aimed to analyze the impact of the two types of variables on the perceived efficacy of musical behaviors to fulfill adults’ emotional wellbeing-related goals during the lockdown established in Spain. Personal variables incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 68 publications
(194 reference statements)
3
45
1
Order By: Relevance
“…Importantly, the survey was gathered in the months of July to-October 2020 with some countries experiencing relief after the first lockdown, others still in lockdown, and yet others seeing a rise in cases toward a second lockdown. Therefore, results for specific countries may show patterns that deviate from the overall results presented here (see Martínez-Castilla et al, 2021).…”
Section: Limitations and Future Directionscontrasting
confidence: 78%
“…Importantly, the survey was gathered in the months of July to-October 2020 with some countries experiencing relief after the first lockdown, others still in lockdown, and yet others seeing a rise in cases toward a second lockdown. Therefore, results for specific countries may show patterns that deviate from the overall results presented here (see Martínez-Castilla et al, 2021).…”
Section: Limitations and Future Directionscontrasting
confidence: 78%
“…These effects were, however, fully mediated by the perceived importance of music (Martínez-Castilla et al, 2021), which was significantly higher in younger and musically trained individuals (cf. Granot et al, 2021). Relatedly, Fink et al (2021) found this factor to be amongst the six strongest predictors of pandemic coping with music.…”
Section: Moderating Factorsmentioning
confidence: 90%
“…Survey studies on qualitative motivations for engagement and perceived coping efficacy of music suggest that this was not the case. During the pandemic, music was used for coping by at least half of the general population (Cabedo-Mas et al, 2021;Fink et al, 2021;Kiernan et al, under review;Martínez-Castilla et al, 2021;Sameer et al, 2020). While active music-making activities like singing and dancing were deemed the most effective for coping (along with music listening), they were also the most ceased during lockdown (Kiernan et al, under review).…”
Section: Coping Efficacymentioning
confidence: 99%
See 2 more Smart Citations